Medieval Warm Period, Little Ice Age and 20th century temperature variability from Chesapeake Bay - Cronin, Tm; Dwyer, Gs; Kamiya, T; Schwede, S; Willard, Da (Global and Planetary Change, 2003)
We present paleoclimate evidence for rapid (< 100 years) shifts of similar to 2-4 degreesC in Chesapeake Bay (CB) temperature similar to 2100, 1600, 950, 650, 400 and 150 years before present (years BP) reconstructed from magnesium/calcium (Mg/Ca) paleothermometry. These include large temperature excursions during the Little Ice Age (similar to 1400-1900 AD) and the Medieval Warm Period (similar to 800-1300 AD) possibly related to changes in the strength of North Atlantic thermohaline circulation (THC). Evidence is presented for a long period of sustained regional and North Atlantic-wide warmth with low-amplitude temperature variability between similar to450. and 1000 AD. In addition to centennial-scale temperature shifts, the existence of numerous temperature maxima between 2200 and 250 years BP (average similar to 70 years) suggests that multi-decadal processes typical of the North Atlantic Oscillation (NAO) are an inherent feature of late Holocene climate. However, late 19th and 20th century temperature extremes in Chesapeake Bay associated with NAO climate variability exceeded those of the prior 2000 years, including the interval 450-1000 AD, by 2-3 degreesC, suggesting anomalous recent behavior of the climate system.